Plant diversity and population in Mount Kelud, East Java - INGE LARASHATI (Biodiversitas Journal of Biological Diversity, 2004)
Mount Kelud is an upper shed Brantas area which has high potential plant diversity. But the land in that upper shed hadexperienced much erosion. Beside erosion process, human disturbances in the resort added the burdens to the existenceof the vegetation. That is why the existence and condition of the plants must be monitored and studied. Assessment of theplants was conducted through literature studies, field surveys and using quadrate plot methods Oosting (Kent & Paddy,1992) 0.75 ha each at different altitudes (600 m, 800 m and 1000 m) above sea level. The results showed that a totalnumber of 125 species belonging to 94 genera, and 49 families were recorded. All three plots were dominated byDendrocalamus asper and Villebrunea rubescens.Â© 2004 Jurusan Biologi FMIPA UNS SurakartaKeywords: plants, diversity, population, Mount Kelud, East Java.